2019
DOI: 10.1136/rapm-2018-100055
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison between interscalene and costoclavicular blocks for arthroscopic shoulder surgery

Abstract: BackgroundThis randomized trial compared ultrasound-guided interscalene block (ISB) and costoclavicular brachial plexus block (CCB) for arthroscopic shoulder surgery. We hypothesized that CCB would provide equivalent analgesia to ISB 30 min after surgery without the risk of hemidiaphragmatic paralysis.MethodsAll 44 patients received an ultrasound-guided block of the intermediate cervical plexus. Subsequently, they were randomized to ISB or CCB. The local anesthetic agent (20 mL of levobupivacaine 0.5% and epin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 27 publications
2
79
4
2
Order By: Relevance
“…For example, randomized controlled trials of patients undergoing the interscalene brachial plexus block [3,5,6] showed that the incidence of HDP in patients who were administered 5 mL of local anesthetic was 27%-45%, about half that of patients who were administered larger volumes of local anesthetic. Studies using a relatively small volume of local anesthetic (20 mL) reported an incidence of HDP of 0%-9% in patients undergoing SCB [8,32] and a 0% incidence in patients undergoing CCB [22]. The present study also showed that administration of < 25 mL of local anesthetic in CCB resulted in a 0% incidence of HDP.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…For example, randomized controlled trials of patients undergoing the interscalene brachial plexus block [3,5,6] showed that the incidence of HDP in patients who were administered 5 mL of local anesthetic was 27%-45%, about half that of patients who were administered larger volumes of local anesthetic. Studies using a relatively small volume of local anesthetic (20 mL) reported an incidence of HDP of 0%-9% in patients undergoing SCB [8,32] and a 0% incidence in patients undergoing CCB [22]. The present study also showed that administration of < 25 mL of local anesthetic in CCB resulted in a 0% incidence of HDP.…”
Section: Discussionsupporting
confidence: 63%
“…A randomized control trial using 35 mL of local anesthetic for the CCB and a paracoracoid infraclavicular approach reported that the rates of HDP were 8.9% in both groups [30]. Moreover, a recent study using 20 mL of local anesthetic for the CCB and interscalene brachial plexus block in 44 patients found that the rates of HDP were 0% and 100%, respectively [22]. The logistic regression model described in this study showed that the likelihood of HDP is 30-fold lower for the CCB than for the SCB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, regional anesthetic methods are frequently preferred as part of multimodal analgesia to provide better pain control and to reduce the side effects associated with opioids [3]. In shoulder arthroplasty, isolated nerve blocks such as suprascapular and axillary nerve blocks for postoperative analgesia are frequently applied as well as the brachial plexus blocks from the costoclavicular, supraclavicular, and interscalene regions [1,[4][5]. Interscalene brachial plexus block (ISBPB) is accepted as the gold standard in shoulder surgery.…”
Section: Introductionmentioning
confidence: 99%